Interculturalité et apprentissage à distance en formation d’enseignants - Lamprini Chartofylaka; Elisabeth Odacre; Antoine Delcroix (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This study reports on an experiment, carried out within the framework of the “Educational technologies for teaching in context - TEEC” project, putting in collaboration students from the Université des Antilles with students of the Université du Québec à Montréal. These students undertake degree-level studies to become future teachers and both groups of students benefit from a course in history education. The common and specific cultural characteristics of the two territories were used in an educational scenario whose objective was the construction of rigid conceptions on historical social concepts - common in the two training curriculums. A series of synchronous communication exchanges (via videoconferencing) between students shows that they become aware that the same concepts can be taught through different thematic entries, depending on the specific socio-cultural elements of each territory. However, their conceptions remain to a great extent conditioned by the approaches used in the school education program they pursued.